2016
DOI: 10.1093/jscr/rjw215
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroid-induced acute compartment syndrome in all extremities

Abstract: Acute compartment syndrome (ACS) is an uncommon complication of uncontrolled hypothyroidism. If unrecognized, this can lead to ischemia, necrosis and potential limb loss. A 49-year-old female presented with the sudden onset of bilateral lower and upper extremity swelling and pain. The lower extremity anterior compartments were painful and tense. The extensor surface of the upper extremities exhibited swelling and pain. Motor function was intact, however, limited due to pain. Bilateral lower extremity fasciotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
5
1
1
Order By: Relevance
“…Hoffmann's syndrome is a rare condition, and to the best of the authors' knowledge it has not been previously reported in Scandinavia. Fasciotomy in this setting is even more extraordinary, with only a few published cases [1][2][3][4][5]. In contrast to previously published cases, the compartment that was affected in this case report was the dorsolateral compartment of the forearm, whereas the patients in previous reports all presented with compartment syndromes of tibial compartments.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Hoffmann's syndrome is a rare condition, and to the best of the authors' knowledge it has not been previously reported in Scandinavia. Fasciotomy in this setting is even more extraordinary, with only a few published cases [1][2][3][4][5]. In contrast to previously published cases, the compartment that was affected in this case report was the dorsolateral compartment of the forearm, whereas the patients in previous reports all presented with compartment syndromes of tibial compartments.…”
Section: Discussioncontrasting
confidence: 61%
“…However, the patient in this previously reported case also presented with acute compartment syndrome of the lower extremities. The previously described bilateral compartment syndrome of the forearms appeared only the day after bilateral lower extremity fasciotomies were performed [5].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…An increase in energy demand during mild exercise has been associated with increased risk of rhabdomyolysis in patients with uncontrolled hypothyroidism [39]. These systemic implications of hypothyroidism can explain the reported case of all-extremities compartment syndrome reported in 2016 by Musielak et al [40]. Hypothyroidism can cause dislipidemia, which if treated with statins can both in combination cause rhabdomyolysis and concurrent ACS [41].…”
Section: Systemic Diseasesmentioning
confidence: 99%
“…Gode bırakmamasının nedeninin proteinden zengin sıvı olduğu için fibroblastlar tarafından kollagen liflere dönüştürülmesi olduğu öne sürülmüştür. TSH'ın fibroblastlarda glikozaminoglikan sentezini uyardığı bildirilmiştir (18). Diğer yandan T3 ve T4 eksikliği glikozaminoglikanların yıkılımını inhibe etmektedir.…”
Section: öDem Patogeneziunclassified